Dendritic Cells Primed with Paracoccidioides brasiliensis Peptide P10 Are Therapeutic in Immunosuppressed Mice with Paracoccidioidomycosis - Silva, Leandro B. R.; Dias, Lucas S.; Rittner, Glauce M. G.; Muñoz, Julián E.; Souza, Ana C. O.; Nosanchuk, Joshua D.; Travassos, Luiz R.; Taborda, Carlos P. (Frontiers in Microbiology, 2017)
Paracoccidioidomycosis (PCM) is an endemic systemic mycosis in Latin America, with the highest prevalence in Brazil, Colombia and Venezuela. Fungi of the Paracoccidioides genus are etiologic agents of the disease. The 15 amino acid peptide P10 is derived from gp43, the main diagnostic antigen of P. brasiliensis. We previously reported that P10-pulsed dendritic cells (DCs) induce a protective response against P. brasiliensis. Presently, dexamethasone-treated BALB/c mice were intratracheally infected with P. brasiliensis Pb18 to establish the therapeutic efficacy of P10-pulsed DCs. Immunosuppressed and infected animals that received DCs had a reduction in their fungal burden, and this result was most pronounced in mice receiving DCs primed with P10. The efficacy of therapeutic DCs was significantly augmented by concomitant treatment with trimethoprim-sulfamethoxazole. Additionally, primed-DCs with or without the antifungal drug induced a beneficial Th1-biased immune response and significantly reduced tissue damage. In conclusion, these studies with immunocompromised mice demonstrate that P10-pulsed DCs with or without concomitant antifungal drugs are potently effective in combating invasive PCM. These findings support further translational studies to validate the use of P10-primed DCs for PCM in immunocompetent and immunosuppressed hosts.